Structural self-organized holonic multi-agent manufacturing systems - Barbosa, José (2014)
Worldwide systems are increasingly growing into unprecedented complexity levels. This increase of system complexity has to be tackled with new control approaches, where decentralization is playing an important role and particularly the Multi-Agent Systems and Holonic Systems. Despite the benefits of this distribution, new problems arise such as the need for entities coordination. This paper proposes an innovative holonic multi-agent system architecture, named ADACOR2, which sets foundation on the already proved ADACOR architecture. This new control architecture is empowered by a two vector self-organization, called behavioural and structural self-organization. This paper describes the structural self-organization vector, particularizing the need for embedding in it learning techniques and nervousness stabilizer. A futuristic test bed, inspired in a real flexible-manufacturing system, is used to demonstrate the benefits of this vector in the architecture.